2013
DOI: 10.1016/j.devcel.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Pairing Preceding SPO11-Mediated Double-Strand Breaks in Mice

Abstract: SUMMARY How homologous chromosomes (homologs) find their partner, pair and recombine during meiosis constitutes the central phenomenon in eukaryotic genetics. It is widely believed that in most organisms SPO11-mediated DNA double-strand breaks (DSBs) introduced during prophase I precede and are required for efficient homolog pairing. We now show that in the mouse, a significant level of homolog pairing precedes programmed DNA cleavage. Strikingly, this early chromosome pairing still requires SPO11, but is neit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
144
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(155 citation statements)
references
References 45 publications
(88 reference statements)
7
144
3
1
Order By: Relevance
“…2A). These results are consistent with the previous observations (Scherthan et al 1996) but partly contradictory to a recent study that reports the appearance of a transient pairing peak at late premeiotic S phase (see the Discussion; Boateng et al 2013). Under our experimental conditions, the distance between paired FISH signals decreases to <1.35 mm in 45%;60% of zygotene spermatocytes and in >95% of pachytene spermatocytes (Fig.…”
Section: Homolog Pairing Initiates In Early Leptotenesupporting
confidence: 88%
See 3 more Smart Citations
“…2A). These results are consistent with the previous observations (Scherthan et al 1996) but partly contradictory to a recent study that reports the appearance of a transient pairing peak at late premeiotic S phase (see the Discussion; Boateng et al 2013). Under our experimental conditions, the distance between paired FISH signals decreases to <1.35 mm in 45%;60% of zygotene spermatocytes and in >95% of pachytene spermatocytes (Fig.…”
Section: Homolog Pairing Initiates In Early Leptotenesupporting
confidence: 88%
“…2A). This result is contradictory to the previous observation that homolog pairing is abolished in Sun1 knockout spermatocytes (see the Discussion; Boateng et al 2013). Furthermore, FISH chromosome painting assays indicate that the initial chromosome association at the early leptotene stage is delayed in Sun1 knockout spermatocytes (Fig.…”
Section: Homolog Association In Sun1 Knockoutcontrasting
confidence: 88%
See 2 more Smart Citations
“…However, recent findings have shown that homolog pairing is completely abolished in Spo11 −/− spermatocytes suggesting that Spo11 is also required for the DSBindependent initiation of synapsis (Boateng et al, 2013). Absence of the Spo11-dependent homolog pairing and DSB formation leads to oocyte apoptosis during early follicular development, soon after birth (Baudat et al, 2000;Di et al, 2005).…”
Section: Meiotic Recombination Checkpointsmentioning
confidence: 99%